Design construtal de uma atleta em cada cavidade retangular contendo PCM - Becker, Fábio (Universidade do Vale do Rio dos Sinos, 2019)
The use of thermal energy is an efficient form of energy storage and can be applied in various areas such as automotive industry, building industry, solar power plants and electronic components. Of the possible forms of thermal storage, latent heat is the most attractive, because it presents high energy storage capacity at constant temperature. Many studies focus on the use of Phase Change Material (PCM) as a form of energy storage. However, due to its low thermal conductivity, it is necessary to implement techniques of heat transfer enhancement. Among the possible existing techniques, the use of fins is the most widespread. Thus, it is important to analyze the best dimension of them, so that the process in which they are inserted, can be optimized. This work aims to verify the influence of the aspect ratio of a fin in a rectangular cavity, containing PCM lauric acid, in the process of melting. The results were obtained through numerical CFD simulation, using the finite volume method. The mathematical model is based on the equations of mass conservation, amount of movement and conservation of energy, being the phase change process based on the enthalpy-porosity model. The mathematical model was validated with experimental results from the literature and the computational meshes were verified by the GCI method. We simulated 09 fin aspect ratios and 09 fractions between cavity area and fin area, totalizing 78 configurations. With these results the Construtal Design method was applied to determine the optimum aspect ratio for each area fraction, which minimizes the total time of the PCM fusion process. In all the fractions of area analyzed, it was found that the larger the aspect ratio of the fin, the longer the total time of the fusion process. For the same value of aspect ratio, it was found that the larger the fraction of area, the smaller the total time of the process.
Keywords: Materiais de mudança de fase (PCM); Simulação numérica; Design construtal; Razão de aspecto; Phase change materials (PCM); Numerical simulation; Design construtal; Aspect ratio; ACCNPQ::Engenharias::Engenharia Mecânica